Behavioral Model of Prevention Occupational Contact Dermatitis in Pesticide Spray Farmers in Gowa Regency - Harlelawati, Furqaan Naiem, Irwandy, Lalu Muhammad Saleh, Syamsiar S. Russeng, Apik Indarty Moedjiono (International Journal of Advanced Science and Technology, 2020)
Occupational contact dermatitis is one of the most common skin disorders. Farmers have the highest incidence of occupational contact dermatitis. One population at risk of experiencing long-term negative impacts from agricultural activities that are very close to pesticides are spray farmers. This study aims to find a model of occupational contact dermatitis prevention behavior in pesticide spraying farmers in Gowa Regency based on the theory of the Health Belief Model and Theory Planned Behavior.This type of research is analytic observational with cross sectional design. This study used stratified random sampling, namely 97 farmers who sprayed pesticides. Data were collected using a questionnaire then analyzed using PLS (partial least square).The proposed model is obtained with a significant pathway between modifying factors into behavioral beliefs, normative beliefs and control beliefs (self and environment); behavioral beliefs to intention (intention) and behavior (practice); normative beliefs to intention; control beliefs (self) to intention; and control beliefs (environment) to intention and behavior (practice). There are five insignificant pathways, namely between the modifying factor pathway to intentions and behavior (practice), the normative beliefs pathway to behavior (practice), the control beliefs (self) pathways to behavior (practice) and the intention pathway to behavior (practice).Improvement of occupational contact dermatitis prevention behavior can be done by paying attention to behavioral beliefs (attitudes), namely by wearing closed clothing (long-sleeved shirts and long pants), control beliefs (environmental) factors, namely by paying attention to wind direction.